China in the Twenty-First Century : The Awakening of Dragon - Koh, Wen Xin (Universiti Malaysia Sarawak (UNIMAS), 2015)
The rise of China will absolutely be one of the greatest dramas of the twenty-first· century. The rapid development and extraordinary economy growth had shocked the world but change is inevitable, no one knows what happen next, no one can ever predict how the world would be in future. The circumstance which China will face in the next 40 years will differ from those of the last 40 years. Some may say China's importance for global and regional stability and development will continue to magnify. Its international economic, political and cultural influence will continue to grow. On the other hand, other may say China will not overthrow the existing order, where the United States manages to remain its position firmly in the international system. This paper thus aims to analyze whether China can really rise peacefully without insuperable obstacle, even overtaking the United States economy through accessing China's economic performance and evaluating the key constraints on China's future development.